Аutomаtіϲ generаtіon control bаѕeԁ wһale орtimіzatіon algorithm - Wisam Najm Al-Din Abed; Omar A. Imran; Ibrahim S. Fatah (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In the designing and operation of interconnected power systems, automatic-generation-control (AGC) represent an important topic. AGC is responsible for maintaining the balance between generation side and load side via controlling the frequency and active power interchange. A new metaheuristic strategy is proposed in this work for optimal controller tuning in AGC system. Ԝһale Орtimіzatіоn Αlgorithm(WOA) is proposed for optimal tuning of reset integral controller. T he proposed strategy is used for optimal AGC in two-areas interconnected-power system. The proposed tuning strategy is compared with other new metaheuristic optimization strategy termed as Harmony Search (HS). The two-area interconnected power system are simulated based MATLAB-toolbox. From results obtained, it is obvious that, the system transient and steady-state behavior are enhanced greatly under the same conditions. This is due to the use of the proposed optimization technique.  The proposed technique has an advanced and superior feature like, local optimum avoiding, fast convergence ability, and lower search agents and iteration are required. All mentioned features, make this strategy optimal for various optimization problems.